Diffusion in solids and liquids VII : selected, peer reviewed papers from the 7th International Conference on Diffusion in Solids and Liquids, Mass Transfer, Heat Transfer, Microstructure & Properties, Nanodiffusion and Nanostructured Materials (DSL 2011), June 26-30, 2011, Algarve, Portugal - Öchsner, Andreas (Diffusion and defect data. Defect and diffusion forum ;, 2012)
This special issue of Defect and Diffusion Forum contains selected refereed papers which were presented at the 7th International Conference on Diffusion in Solids and Liquids (DSL-2011) held on the 26 to 30th June 2011 at the Hilton Vilamoura, Algarve, Portugal. The goal of the conference was to provide a unique opportunity to exchange information, to present the latest results and review burning issues in contemporary diffusion research. Young scientists were especially encouraged to attend the conference and to establish international links with established scientists.